THE CLAUSE COMPLEX CONSTRUCTIONS REALISED IN THE SHORT STORY ENTITLED â€œTHE WITCHâ€™S BREWâ€ - Sri Kurnia Sarip; Yusuf Hidayat (Journal of Applied Linguistics (ALTICS), 2019)
Systemic Functional Linguistics (SFL) is the choice of analysis theory offering the effective tools to analyse the language difficulties and vagueness. One of the systemic analysis tools is clause complex which can simplify the structural and grammatical meanings of the analysed texts through the use of taxis systems and logico-semantic relations (Sagheer Eid, 2016). The proposed study is aimed at analysing systemic functional analysis of clause complex realised in a short story adopting Hallidayan linguistics perspective. The short story is taken from the collection of short stories entitled â€œThe Whispering Knightsâ€ by Clare West. From the aforementioned short stories collection, the writers take a short story entitled â€œThe Witchâ€™s Brewâ€ written by Penelope Lively. By means of a descriptive study under Systemic Functional Linguistics theory as suggested by Halliday & Matthiessen (2014), the writers employ the analysis of taxis systems which cover elaboration, extension, and enhancement. Besides, logico-semantic relation is also analysed which covers projection and expansion. The findings reveal that there are 158 clause complexes which consist of 58 clause complexes of parataxis which are realized 37%, and 40 clause complexes of hypotaxis which are realised 25.3%. In conclusion, the short story is written by the dominant of parataxis then hypotaxis constructions.